Recent Progress in Textile-Based Flexible Supercapacitor - Ghouri, Awais Sattar; Aslam, Rabya; Siddiqui, Muhammad Saqib; Sami, Syed Kamran (Frontiers in Materials, 2020)
In backdrop of growing requirement of flexible and wearable energy storage systems, textile- based supercapacitors having good flexibility, durability, superior charging-discharging rates, high power densities, cost-effective is of crucial importance in the field of wearable electronics. Applicability of cost effective, wearable and flexible textile-based supercapacitors having both synergetic effect of electric double layer capacitance combined with pseudocapacitance of conducting polymer having good electroactivity, thermal and environmental stability, repeated usability with negligible degradation is desired. Herein, supercapacitor based upon textile fabrics will be reviewed from the perspective of electrochemical , mechanical, and thermal properties without compromising flexibility, durability, and comfort of textile fabric.